Analysis of Student Religiosity with Rasch Modeling - Shufufah, Rizqiyah; Sari, Eva Dwi Kumala; Rustam, Ahmad; Mursyidi, Wathroh (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sulawesi Tenggara, 2025)
This research is motivated by the moral degradation among children and adolescents. Religiosity can direct adolescents to behave better in everyday life in accordance with religious teachings. This type of research is a descriptive survey that aims to explain or record conditions or an attitude in order to carry out what is happening now. The sampling technique in this study was to use a cluster random sampling technique. The number of samples in this study amounted to 200 students of SMPN 2 Bekasi City, taken from 5 classes. The instrument used is a Likert model scale, which contains student religiosity. Furthermore, the data analysis technique uses Rasch modeling with the help of Winstep software. The results showed that of the five dimensions of student religiosity analyzed, students of SMP Negeri 2 Bekasi City students were lacking in the ideology dimension (belief / Aqidah); this can be seen from several items that are not FIT/misfit